(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Malaria is nowadays one of the most serious health concerns in a global scale and, although there is an evident increase in research studies in this area, pointed by the vast number of hits and leads, it still appears as a recurrent topic every year due to the drug resistance shown by the parasite exposing the urgent need to develop new antimalarial medications. In this work, 38 molecules were synthesized via copper(I)-catalyzed alkyne-azide cycloaddition (CuAAC) or “click” chemistry, following different routes to produce 2 different organic azides, obtained from a 4,7 dicholoquinoline, reacted with 19 different commercially available terminal alkynes. All those new compounds were evaluated for their in vitro activity against the chloroquine resistant malaria parasite Plasmodium falciparum (W2). The cytotoxicity evaluation was accomplished using Hep G2 cells and SI index was calculated for every molecule. Some of the quinoline derivatives have shown high antimalarial activity, with IC50 values in the range of 1.72–8.66 µM, low cytotoxicity, with CC50>1000 µM and selectivity index (SI) in the range of 20-100, with some compounds showing SI>800. Therefore, the quinolinotriazole hybrids could be considered a very important step on the development of new antimalarial drugs.